Pembuatan Olahan Makanan dari Ikan Sampah Serta Pemasarannya Bagi Nelayan dan Istri Nelayan di Desa Bagan Percut Kabupaten Deli Serdang - Rahmiati Rahmiati; Zulfikar Sembiring; Chalis Fajri Hasibuan (Pelita Masyarakat, 2020)
Most of the people in the Bagan area, Percut Sei Tuan Subdistrict, North Sumatra, are mostly fishermen, almost 80% of the people work as fishermen, which is done by the head of the household in the area. The Bagan area of Percut Sei Tuan District has a lot of catches of trash fish that are only thrown away by fishermen, even though the trash fish has a high protein content and can be processed into processed food such as brains, peanut butter and so on which can improve the economy of the people in Bagan. . The large number of trash fish caught by fishermen and not being utilized optimally resulted in the garbage fish only becoming waste and causing odors and diseases around the fishing community settlements in Bagan Percut, the inability of the community to turn the trash fish into processed food and be worth selling it resulted in an economic level. The fishing community has not increased, with training on how to make processed food from trash fish, training on good and proper packaging and marketing training using internet media, it is hoped that in the future fishermen families can improve their economic level for the better.